Analisis Kekuatan Konstruksi Bejana Tekan Terhadap Tekanan Hydrostatic Test - Jasmid Edy; Adi Mahdi N (JURNAL POWERPLANT, 2013)
Pressure Vessel (Pressure Vessel) serves as a holding tank for pressurized fluid and the tank usually play an important role in industrial companies. In the design of Pressure Vessel in addition to perform calculations and manufacturing processes, also conducted a test called Hydrostatic Test. Hydrostatic testing is one of the provisions of the standard used is ASME Section VIII Division 1 Edition 2010, aims to find leaks in Pressure Vessel. Hydrostatic Test Pressure on process is higher than the operating pressure, therefore there will be a large voltage to the material. In this thesis the author will analyze the magnitude of the voltage comparison between the yield stress material with a maximum voltage that occurs when the Hydrostatic Test.